(3GdMGTjI GdaQOjI ddQSGdI GdMSjfjIs - (3Ydj GdaQOi Hf eUWai GdbjUQis ((3eMeO Hf Ydi s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje CeG HYO ajbhd Ydi GdaQOi Hf eUWai GdbjUi deG cGfJ GdQSGdI GdMSjfjI ai GdBOGH eJOGhdI Hjf GdWdGH hSejJgG HGdMGTjI GdaQOjI ddQSGdI GdMSjfjI s
(3BNQgG (B:s
(3ade jMJL Edi GdESJKfGA JeJ GdMGTjI GdeTJgQI HGdaQOjI GdhGbYI Ydi GdQSGdI GdeTJgQI HGdMSjfjI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs